The Cultural History of the Chinese Concepts Fengjian (Feudalism) and Jingji (Economy) - Feng, Tianyu. author. aut Link
XV, 157 p. 12 illus.
Keywords: This book interprets the typical Chinese concepts of fengjian (feudalism) and jingji (economy) by reviewing the mistranslation and mismatching of concepts from ancient to modern times, from a Western language to Chinese, and exploring Chinese and Western acculturation, which is in line with Mr. Chen Yinque’s theory—”To interpret a Chinese character is to write a history of culture.” In the coordinates of time and space for the transformation of Chinese concepts from ancient to modern times and their translation from Western languages, this book explores the generation and evolution of Chinese concepts; using the semantic window of Chinese characters, the book reviews the historical and cultural connotations of the semantic changes and the history of the long-lasting culture of Chinese characters. This volume moves from reviewing the semantic changes of fengjian and jingji to elaborating concepts of thought; it makes the study of the history of terms and concepts the study of the history of culture and thought; it analyzes words as part of cultural history to welcome the era of cultural and historical research with a focus on words. This book is both scholarly and readable, satisfying both the academic needs of specialized researchers and the cultural curiosity of those with secondary education or above. Feng Tianyu (January 12th, 2023), an expert in Chinese culture and history, senior professor at Wuhan University, who used to be the director of Research Centre of Chinese Traditional Culture at Wuhan University (the Key Research Base of Humanities and Social Sciences of Ministry of Education) and the head of the Innovation Base of Chinese Traditional Culture and Its Modern Transformation. He was the member of the Social Science Committee of the Ministry of Education, vice-president of Association of Chinese Historians, deputy director of Academic Committee at Wuhan University, and deputy chief-editorof local chronicles of Hubei province and Wuhan city. In recent decade, Prof. Feng focused on the study of the modern transformation of Chinese culture under the circumstance of the interaction between Chinese and Western cultures. His works achieved the first prize of China Book Award, the second prize of Outstanding Achievements in Humanities and Social Sciences Research from Ministry of Education and other prizes. Some of his papers have been published abroad in foreign languages, such as in Japanese, English and Spanish.